India–Africa Partnerships for Food Security and Capacity Building
XLIII, 430 p. 33 illus., 29 illus. in color.
Keywords: This is an empirically rich, theoretically grounded and timely analysis of an important aspect of the political economy of South-South relations. -Seifudein Adem, Professor, Graduate School of Global Studies, Doshisha University, Japan. This book makes a valuable contribution in outlining ways for India and Africa to work together towards ensuring greater food security. -Philani Mthembu, Executive Director, Institute for Global Dialogue, University of South Africa, Pretoria, South Africa. This volume showcases the ongoing trends and challenges in South-South cooperation between India and select countries in Africa, for achieving food security and poverty reduction. Scholars and practitioners share diverse perspectives on the role of India’s development compact; aid, trade, private sector driven Foreign Direct Investments (FDIs), and concessional Lines of Credit (LOCs) to the agricultural and agro-processing sectors in Africa. India- Africa cooperation also underscores that the sharing of knowledge and capabilities -technical and financial, along with North- South partnerships- through trilateral and multilateral mechanisms, can upscale the agriculture and agro-processing sectors, address the food security agenda, and reduce poverty. The axial questions in this volume explore how cooperation between India and countries in Africa impact intra-South trading, capacity building, and the investment landscape. Renu Modi is Professor and former Director at the Centre for African Studies, University of Mumbai Meera Venkatachalam is Research Affiliate at the Indian Diaspora Centre and Centre for African Studies, University of Mumbai.